ANALISIS KEBUTUHAN BELAJAR BAHASA INGGRIS MAHASISWA PROGRAM STUDI PARIWISATA - Mulyono, Andreas Aris Eko (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2023)
Need analysis played a vital role in an ESP course design since it became an instrument employed to collect information about the students’ wants, needs, and lacks in their English learning This study was aimed at investigating the language needs of Tourism Department Students. Collecting the data, a questionnaire was administered to 40 Tourism Department students of Institut Teknologi dan Bisnis Kristen Bukit Pengharapan. The Need Analysis revealed that the students’ main objective in learning English was to facilitate them to pursue a professional career in the hospitality and tourism industry. Therefore, they had a deep concern about developing their speaking skills. Although the other language skills were considered important, their development should be in line with their professional career development. It was expected that the result of the Need Analysis could be exposed in the development of English course materials for tourism department students.